Research Paper: Designing a Broadband Achromatic Quarter Wave System in the Visible Region - Masoud Kavosh Tehrani; Mohammad Reza Nejat (فیزیک کاربردی ایران)
The phase delay in wave plates is wavelength- dependent, producing the desired delay only for specific wavelengths of light. This study aims to design achromatic quarter- wave systems that produce a 90-degree phase delay across the entire visible spectrum. It is possible to create an achromat system by combining multiple wave plates. This work has been investigated using two, three, and four- wave plates. This design has been optimized using a merit function known as the degree of achromatization. The degree of achromatization calculates the difference between the obtained and desired phase delays, which should be minimized in the optimization. In this research, birefringent crystals of quartz, calcite, and sapphire have been used. And the thickness, angles between the sharp axes of the plates and the degree of achromatization were obtained using the Quasi-Newton method for the spectral region of 400-700 nm. The results of this research are compared with the work of others and show that the results obtained in the wavelength region of 400-700 nm are better.